Gambaran Jumlah Eritrosit pada Sedimen Urin Pasien Tuberkulosis - Supriyatin Supriyatin; M. Ibnu Ubaidillah; Usdiyanto Usdiyanto; Ade Meli (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
Tuberculosis is still one of the deadliest diseases in the world. Patients with tuberculosis will be given ati-tuberculosis drugs for 6 months. The administration of anti-tuberculosis drugs has 2 phases, for the intensive phase given for 2 months and for the continuation phase given for 4 months. There are types of anti-tuberculosis drugs that have nephrotoxic side effects. If the kidneys, especially the glomerulus, are not functioning properly, erythrocytes can be found in the urine. Normally, erythrocytes in the urine are 0-4 cells/LPB. If more than 0-4 cells/LPB it is called hematuria. This study aims to determine the description of the number of erythrocytes in tuberculosis patients at Arjawinangun Regional General Hospital. In this study using descriptive research method. This study was conducted using a microscopic examination method where urine will be centrifuged first and then made preparations using glass objects and covered with cover glass and viewed using a microscope with a magnification of 40x at least 10 Large Fields. The sampling technique in this study was total sampling. The population in this study were all outpatient TB patients at Arjawinangun Regional General Hospital. Based on the results of urine sediment examination at Arjawinangun Regional General Hospital, data on urine erythrocyte levels in tuberculosis patients obtained the lowest value of 0-1 cells / LPB. The highest value is 12-16 cells/LPB. The average value is 0-2 cells/LPB. The percentage of tuberculosis patients at RSUD Arjawinangun whose erythrocyte levels were positive was 13.3%.